Studies on Fermentation of Monascus purpureus TISTR 3090 With Bacterial Cellulose From Acetobacter xylinum TISTR 967 - Ochaikul*, Duangjai; Chotirittikrai, Karuna; Chantra, Jiraporn; Wutigornsombatkul, Sinith (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Bacterial cellulose produced by Acetobacter xylinum TISTR 967 was fermented by Monascus purpureus TISTR 3090 in culture medium on a rotary shaker at 150 rpm, 30 ˚C for 12 days. Sucrose concentration of 5% (50 g/l), ammonium nirate concentration of 1.5%, initial pH at 5.5 and a temperature at 30 ˚C resulted in the production of an appealing bright red color. The color stability study was carried out using a medium composed of 5% sucrose, 1.5% ammonium nitrate and initial pH 5.5 for fermentation at 30 ˚C for 12 days. Products demonstrated good resistance to washing, heat, freezing, acidification and irradiation. Keywords: Bacterial cellulose, Fermentation, Monascus purpureus Corresponding author: E-mail: Kodaungi@kmitl.ac.th